Influence of sucrose reduction on fouling during the production of dulce de leche. Issue 4 (10th November 2021) - Mauricio, Erica F.; Francisquini, Júlia D. A.; de Paula, Igor L.; de Cezarino Junior, José C. C.; de Oliveira, Luiz F. C.; Stephani, Rodrigo; De Carvalho, Antônio F.; Perrone, Ítalo T.
Abstract: In this Research Communication we focus the food industry´s broad tendency to decrease sugar content in food products onto dulce de leche (DL) and examine the influence of sucrose reduction on the detrimental deposits formed during the production process. The method used to identify the impact produced directly on the heat exchanger during the production of this product with low sucrose content required varying the quantity of sucrose in the milk. Different percentages of sucrose (20, 15, 10, 5 and 0% w/w) were submitted to the DL concentration process in a process simulator. After concentration, the quantification of the deposits formed in each was carried out and these deposits were characterized according to their composition. Methods such as Kjeldahl, Pregl-Dumas and sem -EDS were used. Thus, the work highlights the need to change the product manufacturing process due to changes in the formulation that directly impact the formation of deposits in the equipment used (fouling). This deposit changes significantly in relation to its quantity as well as in relation to the composition and chemical characteristics as the gradual reduction of the sucrose content in the production takes place. Therefore, these impacts must be considered in order to maintain better manufacturing and ensure efficient cleaning of equipment.